1974
DOI: 10.1007/bf01222001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for decreased sensitivity to glucose of isolated islets from spiny mice (Acomys cahirinus)

Abstract: Summary. Immunoreactive insulin (11%1) release from collagenase isolated pancreatic islets of spiny mice (Acomys cahirinus) was examined in 15 rain and 2 h incubations at glucose concentrations between 2.8 and 56 mlVi. The resultant glucose-insulin dose-response curves for Acomys islets were compared to those for similarly incubated rat. islets. After 15 mill incubations, IgI release from Acomys islets was significantly lower than that from rat islets at all stimulating glucose concentrations. After 2 h incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

1975
1975
2000
2000

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Furthermore, even when this is adhered to, differences noted between species must be interpreted cautiously: what is 'normal' for one species may not be normal for another. With these restrictions in mind, studies have been performed on proinsulin synthesis in islets of Langerhans from Acomys cahirinus, the spiny mouse, in which insulin release is markedly insensitive to glucose, when compared with other rodents such as rats or mice [6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, even when this is adhered to, differences noted between species must be interpreted cautiously: what is 'normal' for one species may not be normal for another. With these restrictions in mind, studies have been performed on proinsulin synthesis in islets of Langerhans from Acomys cahirinus, the spiny mouse, in which insulin release is markedly insensitive to glucose, when compared with other rodents such as rats or mice [6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…These differences in the response profile to glucose have been detected in vivo, after either intraperitoneal [4][5] or intravenous [6] glucose injection, and in vitro, using isolated islets [7][8][9]. While acomys islets respond slowly to glucose, the total release of insulin over a two hour period may be comparable to that of rats, at least at higher glucose concentrations [7][8][9], suggesting predominantly early decreased sensitivity to glucose. Indeed, when the early and late release phases were compared in some detail [7][8][9], it was confirmed that the early phase (1-10 rain) of insulin release from acomys islets exhibited both decreased sensitivity to glucose and a decreased release capacity.…”
mentioning
confidence: 99%
See 3 more Smart Citations